By A Woman Writt - Goulianos, Joan. (Baltimore Penguin Books, Inc, 1974)
This book is a unique collection of writings by and about women of six different centuries. When women wrote, they touched upon experiences rarely touched upon by men, they spoke in different ways about these experiences, they often wrote in different forms. Women writers often wrote about themselves as writers--about the discrimination against them and the pain and courage with which they faced it.
Keywords: Literature